Optimalisasi Prestasi Belajar Pendidikan Kewarganegaraan Melalui Pendekatan Pemahaman Konsep di SMP - Kristanto, Agus (Jurnal Manajemen Pendidikan, 2015)
This research aim to description about improvement of domination of matter comprehends   democracy  and  goverment  system  in  Indonesia  through  understanding   of concept at class student VIII F in State Junior High School Three Teras Region Boyolali even semester  of school  year 2013/2014.  Subject  and research  data source  is 24 students.  Data collecting method applies observation,  questionnaire,  documentation,  and test. Data analysis applies critical analysis and comparability. Indicator success of using minimal limit criteria 75 and complete target of 100%. Research procedure applies cycle. Result of inferential research and solution  as follows  : obtained  progress  of achievement  of student  learning  in study of Education   Citizenship   with  matter  comprehends   democracy   and  goverment   system  in Indonesia , at precycle average of 71,6 and cycle I average of 76,2 and cycle II average of 84,8. From this data, seems to explain that happened increase of average of value from precycle to cycle I 4,6 numbers (6,4%), from cycle I to cycle II happened increase 8,6 numbers (11,3%), from pasiklus  to cycle II happened  increase  13,2 numbers  (18,4%).  Highest  value of phase precycle 80 and cycle I 86 and cycle II 92. Seems to explain that from phase precycle to cycle I happened increase equal to 6 number (7,5%), from cycle I to cycle II happened increase equal to 6 number (7%), and from precycle to cycle II happened increase 12 numbers (15%). Low value of phase precycle is obtained by 66 and cycle I 72 and cycle II 76. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 6 number (6,1%), from cycle I to cycle II happened increase equal to 4 number (5,6%), and from precycle to cycle II happened increase  10 numbers  (15,2%).  Complete  percentage  learnt  starts  from precycle  is obtained equal to 21% and cycle I is obtained  equal to 50% and cycle II equal to 100%.  Seems to explain that from phase precycle to cycle I happened  increase equal to 29%, from cycle I to cycle II happened increase equal to 50%, and from precycle to cycle II happened increase equal to 79%.